Diphtheria transmission dynamics: a sensitivity analysis. - George, Isobeye (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
In this paper, sensitivity analysis of the transmission dynamics of the diphtheria model is considered, using an SIR model. The sensitivity indices of the model parameters were calculated. The study was undertaken to ascertain the parameters that should be considered as targets for intervention strategies. The result shows that an increase in the population of susceptible individuals knowing their infectious status (????), the natural death rate (????), the proportion of aware susceptible persons who have been vaccinated (∅), the rate of treatment of diphtheria infectives (????) and, the disease-induced death rate of infectives (????) will decrease the reproduction number (the response function) thereby curtailing the spread of the disease. while a decrease in these parameters will increase the reproduction number which will result in an escalation of the disease. Similarly, if the recruitment rate (????), the incidence rate of unaware susceptible individuals (????1), the incidence rate of aware susceptible individuals (????2), the modification parameter (????) and the disease-induced death rate of treated diphtheria infectives (????) are increased in value, then the reproduction number will increase and this will lead to an endemic situation. It is recommended that relevant government agencies should closely monitor the sensitivity indices.